Mapping research on European VET policy with a systematic literature review method: A pilot study - Ianina Scheuch; Sandra Bohlinger; Anne Bieß; Hoang Long Nguyen (International Journal for Research in Vocational Education and Training (IJRVET), 2021)
Purpose: A systematic literature review has neglected for years in both national and international vocational educational and training (VET) policy research. Recently, scholarly interest in and the need for such a review has increased rapidly. This review introduces the application of the systematic literature review method, with a focus on research work completed in European VET policy. Approach: To investigate the value and applicability of the systematic literature review method in European VET policy research, we conducted a pilot study following the guidelines and procedures presented by Gessler and Siemer. Findings: First, the process of conducting a literature review and its major methodological steps are described, followed by a descriptive analysis of the sample and characteristics of the studies reviewed. Second, initial insights into the research methodology and the topics that emerged during its application are presented. Altogether, we documented a first attempt to systematize research on European VET policy, including lessons learned from conducting a systematic literature review. Conclusion: The review revealed that although research on international European VET policy research has increased in recent years, hardly any systematization of the current research has been proposed. Instead, most research has been limited to identifying specific country-related factors. By comparison, we propose a systematic approach to reviewing research on European VET policy, being well aware of the strengths and limitations of the proposed method and the results. Thus, this systematic review presents a substantial starting point and research agenda for further studies on this topic.
Keywords: 330; Systematic Literature Review; Education Policy; Europe; VET; Pilot Study; Vocational Education and Training